2017
DOI: 10.1128/aem.00712-17
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Lactate Negatively Regulates Shewanella putrefaciens CN32 Biofilm Formation via a Three-Component Regulatory System (LrbS-LrbA-LrbR)

Abstract: The capability of biofilm formation has a major impact on the industrial and biotechnological applications of Shewanella putrefaciens CN32. However, the detailed regulatory mechanisms underlying biofilm formation in this strain remain largely unknown. In the present report, we describe a three-component regulatory system which negatively regulates the biofilm formation of S. putrefaciens CN32. This system consists of a histidine kinase LrbS (Sputcn32_0303) and two cognate response regulators, including a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Biofilms have emergent properties that protect their inhabitants' survival in hostile environments, such as those in which the available nutrients have changed (Myszka and Czaczyk, 2009;Zhang et al, 2014;Liu et al, 2017Liu et al, , 2019Wang et al, 2017;Flemming and Wuertz, 2019). Several studies have shown that multiple bacteria form biofilms in response to changes in the types or concentrations of the available carbon sources (Myszka and Czaczyk, 2009;Zhang et al, 2014;Liu et al, 2017). The relationship between nutrient metabolism and biofilm formation is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biofilms have emergent properties that protect their inhabitants' survival in hostile environments, such as those in which the available nutrients have changed (Myszka and Czaczyk, 2009;Zhang et al, 2014;Liu et al, 2017Liu et al, , 2019Wang et al, 2017;Flemming and Wuertz, 2019). Several studies have shown that multiple bacteria form biofilms in response to changes in the types or concentrations of the available carbon sources (Myszka and Czaczyk, 2009;Zhang et al, 2014;Liu et al, 2017). The relationship between nutrient metabolism and biofilm formation is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Second messengers play an important role in various physiological processes in bacteria. The involvement of the second messenger c-di-GMP in biofilm formation is well established in multiple bacteria (Matsuyama et al, 2016;Liu et al, 2017), and regulatory effects of c-di-GMP on biofilm formation have been carefully reviewed (Christen et al, 2010;Dahlstrom and O'Toole, 2017;Krasteva and Sondermann, 2017). Compared to c-di-GMP, which participates in the whole biofilm cycle (from initial attachment to dispersion), the regulatory effects of cAMP-CRP on biofilm formation seem mostly ancillary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HK LrbS responds to the carbon source sodium lactate and triggers the transcriptional regulatory activity of LrbA by phosphorylation, which subsequently upregulates lrbR . Meanwhile, LrbS activates the phosphodiesterase of LrbR, which decreases intracellular c-di-GMP levels, thereby inhibiting biofilm formation (Figure 1C; Liu et al., 2017). The Lrb-three-component and Hno-multi-component signal transduction systems have much more complex regulatory modes in mediating biofilm formation.…”
Section: The Two-/three-/multi-component Signal Transduction Systemmentioning
confidence: 99%
“…Then, the constructed plasmid was transformed into E. coli DH5α and introduced from E. coli DH5α into S. putrefaciens CN32 wild type (WT) using a helper plasmid, pRK2013, by triparental conjugation ( Figurski and Helinski, 1979 ). The conjugation experiment was performed according to a previous study ( Liu et al, 2017a ). Briefly, the donor and recipient strains were conjugated in a 1:1 ratio and spotted on an LB agar plate.…”
Section: Methodsmentioning
confidence: 99%